PERTANGGUNGJAWABAN HUKUM PERUSAHAAN ASURANSI TERHADAP KERUGIAN PENGANGKUT AKIBAT PEMBAJAKAN LAUT - Tarisah Bahasuan; Wisnu Aryo Dewanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Marine transportation insurance plays an important role in ensuring protection of the risk of loss of the carrier through the waterway. This research aims to analyze the responsibility of insurance companies for carrier losses due to sea piracy, especially in the case of sea piracy against the MV Sinar Kudus ship. This research uses normative juridical method with statutory and conceptual approaches. Legal sources consist of primary and secondary legal materials. The results show that insurance companies have a responsibility based on the principle of indemnity to compensate for the loss of the insured object. The MV Sinar Kudus hijacking case shows the complexity of liability, both for material and immaterial losses suffered by the ship owner and its crew. Legal protection of the insured is realized through national regulations and international conventions, such as UNCLOS 1982. This research emphasizes the importance of clarity of clauses in insurance agreements, as well as the need for synergy between national regulations and international law to protect the parties involved in sea transportation.